Effects of Tillage Practices on Water Consumption, Water Use Efficiency and Grain Yield in Wheat Field - Cheng-yan ZHENG; Zhen-wen YU; Yu SHI; Shi-ming CUI; Dong WANG; Yong-li ZHANG; Jun-ye ZHAO (Journal of Integrative Agriculture)
Water shortage is a serious issue threatening the sustainable development of agriculture in the North China Plain, with the winter wheat (Triticum aestivum L.) as its largest water-consuming crop. The effects of tillage practices on the water consumption and water use efficiency (WUE) of wheat under high-yield conditions using supplemental irrigation based on testing soil moisture dynamic change were examined in this study. This experiment was conducted from 2007 to 2010, with five tillage practice treatments, namely, strip rotary tillage (SR), strip rotary tillage after subsoiling (SRS), rotary tillage (R), rotary tillage after subsoiling (RS), and plowing tillage (P). The results showed that in the SRS and RS treatments the total water and soil water consumptions were 11.81, 25.18% and 12.16, 14.75% higher than those in SR and R treatments, respectively. The lowest ratio of irrigation consumption to total water consumption in the SRS treatment was 18.53 and 21.88% for the 2008–2009 and 2009–2010 growing seasons, respectively. However, the highest percentage of water consumption was found in the SRS treatment from anthesis to maturity. No significant difference was found between the WUE of the flag leaf at the later filling stage in the SRS and RS treatments, but the flag leaf WUE at these stages were higher than those of other treatments. The SRS and RS treatments exhibited the highest grain yield (9573.76 and 9507.49 kg ha−1 for 3-yr average) with no significant difference between the two treatments, followed by P, R and SR treatments. But the SRS treatment had the highest WUE. Thus, the 1-yr subsoiling tillage, plus 2 yr of strip rotary planting operation may be an efficient measure to increase wheat yield and WUE.